1999
DOI: 10.1677/jme.0.0220019
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinases play a permissive role in glucose-induced insulin secretion from adult rat islets

Abstract: The role(s) played by protein tyrosine kinases (PTKs) in the regulation of insulin secretion from pancreatic cells is not clear. We have examined the effects of glucose, the major physiological insulin secretagogue, on the tyrosine phosphorylation state of islet proteins, and assessed cell insulin secretory responses in the presence of PTK inhibitors. Under basal conditions islets contained many proteins phosphorylated on tyrosine residues, and glucose (20 mM; 5-15 min) was without demonstrable effect on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 32 publications
0
42
0
3
Order By: Relevance
“…As ISO, sobretudo a genisteína, aumentam a lipólise em adipóci-tos isolados de ratos, e diminuem a lipogênese no tecido adiposo branco de ratas OVX (48). A incubação de adipócitos de ratos com genisteína resultou inibição da conversão da glicose em lipídios na ausência ou na presença de insulina, com subseqüente redução da lipogê-nese (49,50). Outra ação da genisteína é a diminuição da expressão do RNA mensageiro da LPL no tecido adiposo, com conseqüente diminuição na deposição de gordura (44).…”
Section: Isofl Avonas E Adiposidadeunclassified
“…As ISO, sobretudo a genisteína, aumentam a lipólise em adipóci-tos isolados de ratos, e diminuem a lipogênese no tecido adiposo branco de ratas OVX (48). A incubação de adipócitos de ratos com genisteína resultou inibição da conversão da glicose em lipídios na ausência ou na presença de insulina, com subseqüente redução da lipogê-nese (49,50). Outra ação da genisteína é a diminuição da expressão do RNA mensageiro da LPL no tecido adiposo, com conseqüente diminuição na deposição de gordura (44).…”
Section: Isofl Avonas E Adiposidadeunclassified
“…Moreover, signaling by receptor tyrosine kinases has been implicated as a regulatory mechanism in both β cell proliferation (12)(13)(14) and insulin release (9,(15)(16)(17)(18)(19). In particular, insulin/IGF signaling through insulin receptor substrate (IRS) and phosphoinositide 3-kinase (PI 3-kinase) appears to regulate several aspects of β cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies demonstrated that genistein stimulates insulin secretion from a clonal pancreatic ␤-cell line (8) and cultured islets (9,10), whereas other studies have found an inhibitory effect on insulin secretion (11,12). These discrepant data may be the result of variations in the experimental conditions and model used.…”
mentioning
confidence: 98%